High throughput screening and identification of coagulopathic snake venom proteins and peptides using nanofractionation and proteomics approaches. - Julien Slagboom; Marija Mladić; Chunfang Xie; Taline D Kazandjian; Freek Vonk; Govert W Somsen; Nicholas R Casewell; Jeroen Kool (Public Library of Science (PLoS), 2020)
Snakebite is a neglected tropical disease that results in a variety of systemic and local pathologies in envenomed victims and is responsible for around 138,000 deaths every year. Many snake venoms cause severe coagulopathy that makes victims vulnerable to suffering life-threating haemorrhage. The mechanisms of action of coagulopathic snake venom toxins are diverse and can result in both anticoagulant and procoagulant effects. However, because snake venoms consist of a mixture of numerous protein and peptide components, high throughput characterizations of specific target bioactives is challenging. In this study, we applied a combination of analytical and pharmacological methods to identify snake venom toxins from a wide diversity of snake species that perturb coagulation. To do so, we used a high-throughput screening approach consisting of a miniaturised plasma coagulation assay in combination with a venom nanofractionation approach. Twenty snake venoms were first separated using reversed-phase liquid chromatography, and a post-column split allowed a small fraction to be analyzed with mass spectrometry, while the larger fraction was collected and dispensed onto 384-well plates. After fraction collection, any solvent present in the wells was removed by means of freeze-drying, after which it was possible to perform a plasma coagulation assay in order to detect coagulopathic activity. Our results demonstrate that many snake venoms simultaneously contain both procoagulant and anticoagulant bioactives that contribute to coagulopathy. In-depth identification analysis from seven medically-important venoms, via mass spectrometry and nanoLC-MS/MS, revealed that phospholipase A2 toxins are frequently identified in anticoagulant venom fractions, while serine protease and metalloproteinase toxins are often associated with procoagulant bioactivities. The nanofractionation and proteomics approach applied herein seems likely to be a valuable tool for the rational development of next-generation snakebite treatments by facilitating the rapid identification and fractionation of coagulopathic toxins, thereby enabling specific targeting of these toxins by new therapeutics such as monoclonal antibodies and small molecule inhibitors.